Design & aging: Challenges and urgency for the quality of life of a changing society - Gomes, Ilma de Oliveira; Couto, Rita Maria de Souza (Seven Editora, 2024)
This article aims to analyze the impact of population aging on society and was guided by the conviction of the fundamental role that Social Design can play in promoting the quality of life and well-being of the elderly. The ageing of the population is a global reality that brings with it significant challenges and opportunities for public policies, the economy and society as a whole. With the increase in life expectancy and the decrease in the birth rate, the demographic profile of societies is changing rapidly, with an increasing number of long-lived people. This phenomenon presents new challenges, such as the need to adapt health, social security, and urban planning systems to meet the specific needs of seniors. In addition to structural challenges, older people face barriers such as age-based discrimination and social exclusion. The stigma associated with old age often limits this group’s opportunities for participation and contribution in society, which can lead to further isolation and deteriorating mental and emotional health. In this context, Social Design emerges as a powerful tool to promote inclusion and respect for the elderly, facilitating active participation in community life, promoting group connection, a sense of belonging, valuing the contribution of the elderly to society with dignity. Social Design can and should be an essential tool in this process, helping to build a more inclusive and sustainable future for all generations. DOI:https://doi.org/10.56238/sevened2024.010-006